Sumatera Language Interference to Indonesian Language - Rahmatullah (Proceedings of International Conference on Islamic Civilization and Humanities, 2023)
This study has two objectives, namely to describe the forms of Sumatran language interference with Indonesian and to explain the factors that influence it. This study uses a descriptive qualitative approach. The data were obtained by using the listening method with the free-involvement listening technique (SBLC), note-taking, and sound recording techniques. In analyzing the data, the method used is the equivalent method. From the results of the analysis found forms of interference in the field of phonology, namely changes in vowel phonemes such as kulet (skin) and changes in consonant phonemes such as long. The forms of interference in the lexical field found are umah (house) and abih (finished). The forms of interference in the grammatical field are divided into interference in the field of morphology, namely affixations such as banamo (named) and gadang (large) and compounding such as besibanak besipakak (don’t want to hear or be advised) and also interference in the field of syntax, namely assignment words such as eating continuously ( eat first). All these disturbing words are caused by background factors such as bilingualism of speakers, lack of pride in using Indonesian, carrying regional language customs, and lack of Indonesian vocabulary prior to progress and renewal.